Improving Time to Antibiotics for Pediatric Oncology Patients With Suspected Infections: An Emergency Department–Based Quality Improvement Intervention. Issue 1 (January 2018) - Yoshida, Hiromi; Leger, Kasey J.; Xu, Min; Migita, Russell T.; Rutledge, Joe C.; Pollard, Jessica A.; Kroon, Leah; Mazor, Suzan S.; Moon, Andres; Rutman, Lori E.
Abstract : Objective: Studies in pediatric patients with fever and neutropenia demonstrate that shorter time to antibiotics is associated with a decrease in pediatric intensive care unit admissions and in-hospital mortality. In 2012, a 2-phase quality improvement intervention was implemented in a pediatric emergency department (ED) to improve care for this high-risk patient population. The objective was to determine if the introduction of (1) a rapid absolute neutrophil count (ANC) test and (2) a standardized prearrival process decreased time to antibiotics for febrile hematology/oncology(heme/onc) patients presenting to the ED. Methods: The rapid ANC test introduced in February 2012 decreased turn-around-times in the laboratory from 60 to 10 minutes. The standardization of the prearrival communication between the heme/onc team and ED was implemented in August 2012 as part of a clinical standard work pathway for heme/onc patients who presented to the ED with fever and possible neutropenia. Time from arrival to the ED to administration of first antibiotic was measured. Data from January 2011 to December 2013 were analyzed using statistical process control. Results: Seven hundred eighteen encounters for 327 patients were included. After the rapid ANC test, the proportion of patients who received antibiotics within 60 minutes of arrival increased from 47% to 60%. There was further improvement to 69% with implementation of the clinical standard work pathway. Mean time to antibiotics decreased from 83 to 65 minutes (21% decrease). Conclusion: This 2-phase quality improvement intervention increased the proportion of patients who received antibiotics within 60 minutes of arrival to the ED. Similar processes may be implemented in other pediatric EDs to improve timeliness of antibiotic administration.